Integrasi Aplikasi Spiritual "Self-Reminder": Mendukung Kesehatan Mental Remaja Muslim di Era Globalisasi - Angelica Silfana; Riza Riza (Paedagogie, 2026)
The mental health condition of adolescents is important in psychosocial development. In the era of globalization, it has had a significant impact, previously the rapid and flexible acquisition of information through social media provided many challenges and responsibilities for young people so that their energy was focused on doing everything quickly. As a result, many Indonesian youth experience health problems, namely sleep disorders, anxiety, bipolar disorder and depression. So in this research we tried to design a "Self-Reminder" application which functions to make it easier for young Muslims to maintain their mental health by learning spiritual values to maintain their spirituality at work. The aim of this research is to provide an application design that integrates the spiritual values of youth mental health. The substance taken is a way to purify their souls from worldly influences, namely tazkiatun nafs. So, by managing their emotions and souls they can function well at work. The method used in this preparation is a literature study prototype which is a solution to the intended problem by analyzing previous literary sources. The design of this application was developed using smartphone media which can be used at any time as a reminder. The advantages of the application, apart from being flexible, are that the material and discussions about mental health are clear and interesting. Even though it is in the form of readings and video lectures, the points of the discussion are easy to understand and absorb. Apart from that, there are many motivational words that can remind young people to always be steadfast in maintaining the purity of their souls and spirituality in facing the current era of globalization. Therefore, this research tries to design and developing smartphones as a medium not only as a communication tool but also as a tool to commemorate youth mental health with spiritual values.